Examining the Relationship between Corporate Social Performance and Corporate Financial Performance in the Chinese Mining Industry - Jin, Yiquan (2019)
With rising awareness of the need for economic and environmental sustainability, corporate social responsibility (CSR) has attracted increasing attention of all sectors of society (Romani, Grappi and Bagozzi, 2013; Barnea and Rubin, 2010; Habaragoda, 2018). However, most companies only focus on profitability. They are not interested in social responsibility issues as these issues have no close relationship with corporate financial performance (CFP). It is important to investigate whether CSR is value-enhancing as achieving higher level of financial benefits is the main objective of businesses (Ma, 1993; Majeed, 2011). Therefore, the purpose of the dissertation is to explore whether corporate social performance (CSP) has an impact on CFP in the Chinese mining industry. As some researchers (e.g., Saeidi et al., 2015; Galbreath and Shum; 2012; Lai et al., 2010) suggest, CSP may not directly influence financial performance. This dissertation also examines whether reputation plays a mediating role of on the CSP-CFP relationship. Besides, China has a history of making state-owned enterprises (SOEs) shoulder social responsibilities as the government commits a lot of resources to these companies (Zhang et al., 2014). Because of the special role of SOEs in the development of CSR in China, this dissertation also tries to decide whether the SOEs have better CSP. To test the hypothesis, a sample consisted of 69 Chinese listed companies in the mining industry with a period from 2011 to 2016 was used.